THE SOCIO-ECONOMIC CHALLENGES FACED BY CHURCH OF GOD-KENYA IN POVERTY ALLEVIATION IN EMUHAYA DISTRICT, WESTERN KENYA - Hezekiah, Obwoge (European journal of philosophy, culture and religion, 2017)
Purpose: The purpose of the study was to assess the socio-economic challenges faced by CoG-Kenya in poverty alleviation in Emuhaya District, Western Kenya.Methodology: This study was a cross-sectional research that sought to give an examining and descriptive scrutiny of the CoG-K’s activities in Emuhaya District of Western Kenya. This study sampled a total of 312 respondents (1 Bishop, 1 General Secretary, 1 General Assembly Trustee, 1 General Assembly Treasurer, 16 Directors, 282 Pastors, and 10 Elders) through purposive sampling method. Oral interviews, questionnaire methods and focus group discussion were used to collect data from the respondents. Observation method was used to validate the information obtained through oral interviews and questionnaires. Secondary data was sourced from published and unpublished literature. Data was analyzed using the theological method of induction (TMI).Results: The study concludes that as much as the CoG-K has made concerted attempts towards development in Emuhaya District by influencing the peoples thinking on legitimacy of wealth and education, and on the moral value of saving and investing. However some of its programs and ceremonial functions like ordination, baptism, marriage and weddings tend to retard these efforts of alleviating poverty. Although such programs and celebrations serve the poor at the grassroots level, they delay change in behavioural and institutional transformation capable of sustaining economic growth.Unique contribution to theory, practice and policy: There is a need to change cultural practises that tend to retard development among the adherents of the CoG-K in Emuhaya District. The study posits that cultural practices surrounding marriage and death that are repugnant and detrimental to change should be discarded if development is to take place.